The Problem of the Meaning of Human Being in the Philosophy of Jean-Paul Sartre - Rostovskytė, Aneta; Bielskis, Andrius (Problemos, 2014)
The paper critically engages with Jean-Paul Sartre’s philosophical project of Being and Nothingness, especially with the way Sartre articulates the key philosophical question of the meaning of human existence. It argues that the problem of the meaning of being in Sartre’s thought is rooted in the negation of the metaphysical base. To explain this philosophical negation we aim to spell out Sartre’s rejection of the dualism between being and appearance. We argue that Sartre’s philosophical emphases on appearance, on nothingness, and the negation of the consciousness of the Other should be understood against the socio-political background of the mid twentieth century post-war Europe. Sartre’s understanding of the non-authentic and authentic conditions of existence, otherwise known as the individual and non-individual, is also critically discussed. The paper concludes that Sartre’s emphasis on nescience and on radical choice is both philosophically and existentially counterproductive.